RATIONALITY PROFILE THE USE OF ANTIBIOTICS IN THYPOID FEVER PATIENTS AT HOSPITALIZATION BPM CLINIC (BHAKTI PRATAMA MAYANG) - Novi Ahdina (LPPM Universitas dr. Soebandi, 2024)
Background: Typhoid fever is an infectious disease. In Bhakti Pratama Mayang Clinic (BPM) is first from 10 diseases treated, for the first 6 months in 2022. In the treatment, the 3rd generation cephalosporin class is the main choice at BPM clinic. Irrationality in accuracy of the drug, accuracy of the dose, including the duration of antibiotic administration at BPM Clinic may occur. The purpose this study is to provide an overview the rationality using antibiotics in typhoid fever patients. Method: descriptive research design with secondary data population medical record of typhoid fever patients at BPM Clinical Inpatient in 2022. The sample used 96 medical record with total population technique, checklist measuring instrument and data recapitulation sheet with descriptive analysis of frequency distribution and percentage. Results: The types of antibiotics used for typhoid fever inpatients at BPM Clinic are almost all of cephalosporin class, namely most (53%) cefotaxime and (44%) ceftriaxone. The rationality of antibiotics used in typhoid fever inpatients all rational, namely Right Diagnosis, Right Patient, Right Route of Administration, and almost all for Right Dosing Regimen (95%) and Right Time of Administration (88%). Discussion: Chloramphenicol is the first-line antibiotic for the treatment for typhoid fever, in BPM Clinic 3rd generation cephalosporin used. Conclusion: Cephalosporin class (cefotaxim and ceftriaxone) are the main choice of antibiotics for typhoid fever patients at BPM Clinic and the rationality of giving antibiotic therapy for 3 appropriate ones is all 100% (Diagnosis, Patient, Route of Administration), and the other 2 are almost all for the Dosage Regimen (95%) and duration of administration (88%)